2021
DOI: 10.1177/02646196211019064
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for quality of life and related outcomes among unpaid caregivers of older adults with visual impairments: A scoping review

Abstract: Unpaid family caregivers play a critical role in the care of older adults with visual impairments. Caring for older adults with visual impairments requires much time and energy, often resulting in psychological stress and reduced quality of life for the unpaid caregiver. However, there is a paucity of data on the impact of caregiving on quality of life and related outcomes among these caregivers. The purpose of this study was to conduct a scoping review examining issues of quality of life, health, stress, burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…This finding may relate to the characteristics of the sample utilized in this study, including their relatively youthful age, types of care provided to the older adults with visual impairments (i.e., only about 20% provide daily care), as well as the duration of time the family caregiver had been in their role (i.e., more than 53% had been in the role for less than 3 years). Older age, more time spent providing care, and longer duration as a family caregiver have all been shown to negatively impact family EQ-5D and related outcomes, including well-being (Hazzan et al, 2021a(Hazzan et al, , 2021bHeesterbeek et al, 2017;White et al, 2004). Among other implications, this may be the reason for the high percentage (77.69%) of family caregivers who said they were satisfied with their lives as well as those who indicated that they are in good spirits most of the time (72.31%).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding may relate to the characteristics of the sample utilized in this study, including their relatively youthful age, types of care provided to the older adults with visual impairments (i.e., only about 20% provide daily care), as well as the duration of time the family caregiver had been in their role (i.e., more than 53% had been in the role for less than 3 years). Older age, more time spent providing care, and longer duration as a family caregiver have all been shown to negatively impact family EQ-5D and related outcomes, including well-being (Hazzan et al, 2021a(Hazzan et al, , 2021bHeesterbeek et al, 2017;White et al, 2004). Among other implications, this may be the reason for the high percentage (77.69%) of family caregivers who said they were satisfied with their lives as well as those who indicated that they are in good spirits most of the time (72.31%).…”
Section: Discussionmentioning
confidence: 99%
“…Providing care for older adults with chronic illnesses and disabilities is incredibly stressful, and many family caregivers feel enormous pressure to provide the best possible care for their loved ones (Hazzan et al, 2021a(Hazzan et al, , 2021b. As the population of older adults in the USA increases, the prevalence of chronic illnesses and disabilities, including visual impairment, is expected to rise (Mather et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations